Bacteriocin-Producing Probiotic Lactic Acid Bacteria in Controlling Dysbiosis of the Gut Microbiota - Anjana,; Tiwari, Santosh Kumar (Frontiers in Cellular and Infection Microbiology, 2022)
Several strains of lactic acid bacteria are potent probiotics and can cure a variety of diseases using different modes of actions. These bacteria produce antimicrobial peptides, bacteriocins, which inhibit or kill generally closely related bacterial strains and other pathogenic bacteria such as Listeria, Clostridium, and Salmonella. Bacteriocins are cationic peptides that kill the target cells by pore formation and the dissipation of cytosolic contents, leading to cell death. Bacteriocins are also known to modulate native microbiota and host immunity, affecting several health-promoting functions of the host. In this review, we have discussed the ability of bacteriocin-producing probiotic lactic acid bacteria in the modulation of gut microbiota correcting dysbiosis and treatment/maintenance of a few important human disorders such as chronic infections, inflammatory bowel diseases, obesity, and cancer.